2015
DOI: 10.1093/nar/gkv814
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 affects splicing profiles and isoform production of genes involved in the apoptotic and mitotic cellular pathways

Abstract: In recent times, high-throughput screening analyses have broadly defined the RNA cellular targets of TDP-43, a nuclear factor involved in neurodegeneration. A common outcome of all these studies is that changing the expression levels of this protein can alter the expression of several hundred RNAs within cells. What still remains to be clarified is which changes represent direct cellular targets of TDP-43 or just secondary variations due to the general role played by this protein in RNA metabolism. Using an HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 72 publications
5
68
0
Order By: Relevance
“…Thus, the analyzed events were the splicing of SKAR/POLDIP3 exon 3 (48); TNIK exon 15 (14); STAG2 exon 30b (49); and MADD exon 31 (49). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the analyzed events were the splicing of SKAR/POLDIP3 exon 3 (48); TNIK exon 15 (14); STAG2 exon 30b (49); and MADD exon 31 (49). …”
Section: Resultsmentioning
confidence: 99%
“…To this aim, we examined the levels of MADD and BRD8 expression levels as these were previously reported to be reduced following the TDP-43 RNAi (49). TNIK was also added as a control, since its splicing levels were affected by most of these hnRNPs.…”
Section: Resultsmentioning
confidence: 99%
“…3c). We also evaluated splicing in TDP-43 target genes POLDIP3/SKAR, STAG2, and FNIP1 [11, 14, 55], but found no changes in their respective splicing profiles (Supplemental Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we examined the exon 31 skipping in MADD gene. MADD gene is one of the previously identified, direct targets of TDP-43, and TDP-43 knockdown in HEK293 cells has been reported to increase the level of exon-skipped MADD gene (28). We transfected EGFP, wt, C71G or M114T mutant PFN1 into HEK293 cells and observed that C71G or M114T mutant PFN1 significantly increased the levels of the exon 31-skipped MADD gene, whereas wt PFN1 did not change the splicing profiles of the MADD gene (Fig.…”
Section: Overexpression Of Fals Mutant Pfn1 Increased the Cytoplasmicmentioning
confidence: 87%
“…6, A and B, 1.55 Ϯ 0.22% in EGFP, 0.96 Ϯ 0.23% in wt PFN1 (p ϭ 0.83), 6.39 Ϯ 0.81% in C71G PFN1 (p ϭ 0.0001), 3.92 Ϯ 0.47% in M114T PFN1 (p ϭ 0.0086)). We also examined exon 7 skipping in the FNIP1 gene, exon 20 skipping in the BRD8 gene, or exon 3 skipping in the SKAR gene (28,29), although no changes in the splicing profiles of these genes were observed among HEK293 cells transfected with EGFP, wt, C71G, or M114T mutant PFN1 (data not shown). Human HDAC6 mRNA has been reported to be down-regulated in TDP-43-silenced HEK293 cells (30).…”
Section: Overexpression Of Fals Mutant Pfn1 Increased the Cytoplasmicmentioning
confidence: 99%